A hybrid banking websites quality evaluation model using AHP and COPRAS-G: a Turkey case - Ecer, Fatih (Technological and Economic Development of Economy, 2014)
The quality of websites can directly influence bank’s effectiveness. Therefore, the effective evaluation of the quality of bank websites is a point of concern for customers, owners, and researchers. The primary goal of the study is to propose a hybrid model of AHP and COPRAS-G methods for evaluating the website quality of banks. Furthermore, this study sheds light on understanding weights of evaluation criteria related to quality of bank websites. In this study, the weights of the evaluation criteria are computed by AHP method. Next, COPRAS-G is used to assess the quality levels of the websites and to rank them. A case study of evaluating the quality of bank websites of seventeen banks in Turkey is used to demonstrate the applicability and the effectiveness of this model. Empirical findings show that banks in Turkey utilize the Internet to its full potential to improve their websites. Furthermore, Garanti Bankasi has the best overall performance, followed by TEB, and Ziraat Bankasi. Additionally, the top-five evaluation criteria in order of importance are relevance, richness, understandability, navigability, and response time. Overall, the results show that this model provides a comprehensive and systematic approach that quantitatively measures a website’s quality. First published online: 08 May 2014